Correlation of trust and work engagement: A modern organizational approach - Ana Nešić; Slavica Mitrovic Veljkovic; Maja Meško; Tine Bertoncel (Amfiteatru Economic Journal, 2020)
In modern organizations, in which changes are happening faster and more unpredictably, employees are gaining a more complex role and increasing importance. New approaches to employee insight, based on the heavy work investment concept (HWI), bring together different theoretical and practical approaches that attempt to explain the causes and consequences of certain organizational behaviors. The fundamental issue is determining whether engagement and trust, remain two of the critical factors of an organizations success, or are their roles in effectively organized systems significantly changed or reduced. This research aims to establish a correlation between trust and work engagement in on 787 respondents from 16 organizations in Serbia. Trust in organizations is measured through the dimensions of benevolence, integrity, competence and predictability. Engagement of employees is measured through the dimensions of energy, dedication and absorption. The results showed a significant correlation between dimensions of trust: benevolence/integrity and competence, with all work engagement dimensions. The strongest correlation is established between the trust dimension of benevolence/integrity and the work engagement dimension - energy. The significance of the research is reflected in the elucidation of behavioral factors of employees in organizations burdened with transitional changes.
Keywords: D23; E24; J22; J53; M12; 330; work engagement; trust; organization; HWI concept; employees; Serbia